Local Government Strategies for Tourism Development at Lhok Bubon Beach in West Aceh Regency - Athirah, Putri; Macella, Agatha Debby Reiza (Pencerah, 2025)
This research aims to discuss the local government's strategy in developing the tourist attraction of Lhok Bubon Beach, West Aceh Regency. This research uses a qualitative method with a phenomenological approach. The results of this study indicate that the local government strategy in developing the tourist attraction of Lhok Bubon Beach has been carried out but has not run optimally. This can be seen from the first indicator, namely attractions; the attraction possessed by Lhok Bubon Beach is extraordinary natural beauty, still maintaining cultural values, lack of information and promotion of historical relics and creating and improving artificial tourism conditions. Second accessibility; the ease of getting to the location of Lhok Bubon Beach can be accessed through google maps, there are direction boards, access roads that have been asphalted around ± 250 metres, but to get to the end of the beach is still difficult to pass, internet network conditions are not optimal and there are still livestock roaming the streets. Third, amenity; the facilities available at Lhok Bubon Beach are still not optimal due to the unavailability of various important facilities that support the tourist experience. Fourth, institutions; the village government has a cooperative relationship with other institutions, but there is still a lack of effective collaboration to develop beach tourism objects. The conclusion of this study shows that although there are efforts in developing the tourist attraction of Lhok Bubon Beach, there are still many aspects that need to be improved so that tourism potential can be maximized.